If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + 8 = 14 + -3x Reorder the terms: 8 + -6x = 14 + -3x Solving 8 + -6x = 14 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 8 + -6x + 3x = 14 + -3x + 3x Combine like terms: -6x + 3x = -3x 8 + -3x = 14 + -3x + 3x Combine like terms: -3x + 3x = 0 8 + -3x = 14 + 0 8 + -3x = 14 Add '-8' to each side of the equation. 8 + -8 + -3x = 14 + -8 Combine like terms: 8 + -8 = 0 0 + -3x = 14 + -8 -3x = 14 + -8 Combine like terms: 14 + -8 = 6 -3x = 6 Divide each side by '-3'. x = -2 Simplifying x = -2
| b+b+b+6=6b+5-2b+9 | | y^2+7y-30=0 | | 4x-2=-2x-56 | | 7x-10=-37-2x | | 8k-6+3k-2k+3=4*33 | | 6-5x-2x=34 | | 6w^2+33w-18= | | 2d-8-5d=-3d-2d+6 | | 15=3.4n-2(n-4) | | (3x)+(4x-24)=180 | | x^2+1045x+14278=0 | | P=100-0.5q | | 3c-6+2c=10c-2c+6 | | 5u+6v-3(3u-2v)= | | 2n-4m=8 | | 12s^2-13st-4t^2= | | 15x-10=-9x+12 | | 10x+1=2x+5 | | 41-8x=-6x-23, | | 3(3x+4)-2-5-7x=20 | | -7q+8-6+5q=8 | | 3x+16=12x-74 | | -r+7r-3+5r=93 | | w=mt+b | | =2(3s-8)+7 | | -(4x-4)-(-2x-6)+3=-3(x-1)-(6x+2)+3 | | 2b-10b-15+5=8b-40-4b-6 | | 10x^4-21x^2+9= | | 6a+3a=18 | | 3x+14+2x+1=180 | | 11a-4a-18=2a+a+10 | | 9x-5x-x=9 |